PENERAPAN PEMBELAJARAN KOOPERATIF TIPE STAD DENGAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN MINAT DAN PRESTASI BELAJAR IPS SISWA KELAS VIII.F DI SMP NEGERI 2 KARANGMALANG KABUPATEN SRAGEN TAHUN PELAJARAN 2014/2015 - Sunarno, S. (HISTORIKA, 2015)
This study aims to increasestudent interest and improve student IPS learning achievement bycooperative learning STAD with audio-visual in F class VIII SMP Negeri 2 Karangmalang in the second semester of academic year 2014/2015.This study uses a Classroom Action Research. Subjects were students of class VIII SMP Negeri 2 Karangmalang Sragen. This data collection is done by using interviews, tests, observation, and questionnaires.Technique authenticity of data by the method of triangulation techniques.Technical analysis is done by collection data, data reduction, data presentation, and conclusion. The research process conducted three cycles, in each cycle includes four stages of action planning, action, observation and reflection.The results showed that: (1) Application of STAD cooperative learning in social studies learning can increase student interest class VIII F SMP Negeri 2 Karangmalang in the second semester of academic year 2014/2015, (2) use of cooperative learning STAD in IPS learning can improve learning achievement  eighth grade students of SMP Negeri 2 Karangmalang in the second semester of academic year2014/2015. Increased student interest can be seen from the results of questionnaire student interest after the action, in cycle 1 reaches 26.5%, cycle 2 increased to 47.1%, and the third cycle increased to 88.2%. While student achievement on the initial conditions shows that the average score is 67.1 with classical completeness 55.9%, after the action on cycle 1 to increase the score of the average is 70.3 with classical completeness of 70.6%, cycle 2 increased average score becomes 73.4 with classical completeness 76%, and in 3 cycles increased, with an average score of 78.4 with classical completeness of 88.2%.